Hubungan Sikap Siswa Tentang Keterampilan Dasar Mengajar Guru Dengan Hasil Belajar Siswa Pada Mata Pelajaran Biologi Di Sekolah Menengah Pertama Negeri 28 Mesumai Kabupaten Merangin - Eko Wulandari (BIOCOLONY, 2018)
A skilled teacher who is able to develop his basic teaching skills will assist students in understanding the material presented by the teacher. The learning process takes place regardless of the basic skills of teaching teachers. This is seen from students or students who are only asked to record and do the tasks contained in the manual without the description of first explanation. So that learners get a lesson directly from the manual without any process of question and answer and explanation of the material. From the calculation seen that r counted for 0.736 while r table of 0.325 thus the correlation coefficient r count / robservasi greater than r table (0.736≥0,325) so it is concluded that Ha accepted with statement there is positive relation between variable X with variable Y at SMPN 28 Mesumai regency merangin. From the data obtained can be seen that r arithmetic of 0.736 if consulted with r table of 0.325 at a significant level of 95% then (rhit 0.736> rtab 0.325). R count is greater than r table, it shows a positive correlation between student's attitude toward basic skill of teacher teaching with student learning result of biology subject on concept of respiratory system in human.